2021
DOI: 10.1088/1755-1315/922/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CO2emissions in Indonesia

Abstract: This study was conducted to examine the effect of the variable use of CO2 emission gas and export variables on Indonesia’s economic growth. The data used in this study are time series data from the two variables for the period 2004 to 2019. All data were obtained from the world bank and accessed through the www.data.worldbank.org. The data analysis method used in this study uses an autoregressive distributed lag (ARDL) model approach. The ARDL model is used to examine the short-term and long-term effects of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The increased use of fossil energy and combustion in the agricultural sector has contributed significantly to environmental deterioration and rising CO2 emissions in Peru [18]. [19] said government requires the use of CO2 to increase the sustainability of its development. [16] also found that rapid urbanization with deforestation significantly increased CO2 emissions and climate change in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of fossil energy and combustion in the agricultural sector has contributed significantly to environmental deterioration and rising CO2 emissions in Peru [18]. [19] said government requires the use of CO2 to increase the sustainability of its development. [16] also found that rapid urbanization with deforestation significantly increased CO2 emissions and climate change in Malaysia.…”
Section: Introductionmentioning
confidence: 99%